Supervisory roles of the Inspector of schools as perceived by the secondary school teachers in the district of Kuantan, Pahang - Manian s/o Ramasamy (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
This study assesed the perceptions of teachers towards the supervisory roles of the inspector of schools. The teachers' views were sought on what constitutes important supervisory roles, and to what extent it is performed byh the present day inspectors. The subjects for this study were randomly selected from a list of teachers who have been observed by the School Inspectorate from 22 secondary schools in the District of Kuantan. A self-constructed questionnaire was used to estimate the perceptions of teachers towards the supervisory roles ofr the inspector of schols. A tolal of 196 out of 210 teachers were able to participate in this study, representing a response rate of 91.2%. The results of the study indicate that the teachers placed very high importance on those supervisory roles of the inspectors that stimulate professional growth among teachers, encourage proper implementation of curriculum, and provide guidance and advice on suitable teaching methods.